Beyond formal education: Exploring informal apprenticeship as a pathway to entrepreneurial success from a Ghanaian perspective - Mwinkume, Gabriel; Nandakumar, C.D.; Aidoo, Emmanuel; Yeboah, Solomon T. (Edelweiss Applied Science and Technology, 2025)
This study investigates how informal apprenticeships serve as a pathway to entrepreneurship in Ghana, focusing on the factors influencing the decision to enter apprenticeships, trade selection, and entrepreneurial ambitions. Utilizing a multinomial logit model, the research examines data from 1,600 apprentices to identify the interplay between individual characteristics, financial limitations, and trade preferences. The analysis reveals that financial constraints significantly impact the decision to pursue an apprenticeship, while trade selection is largely influenced by perceived entrepreneurial prospects. Interestingly, individuals with higher educational qualifications tend to enter skilled trades, implying that formal education enhances their recognition of business potential in these fields. Contrary to expectations, guidance from parents and teachers appears to discourage apprenticeship participation. Additionally, catering and carpentry emerge as trades with strong entrepreneurial potential, though the limited range of available apprenticeship options presents a challenge. These insights question the notion that informal apprenticeships are primarily for academically weak students, highlighting the importance of strategic interventions to strengthen their role in fostering entrepreneurship. To enhance the effectiveness of informal apprenticeships, policies should focus on broadening trade options, incorporating entrepreneurship education, and strengthening the link between formal and informal learning systems. Further research could explore comparative studies of apprenticeship models across different contexts.